Digital Competence of Educators (DigCompEdu): Level of Digital Competence of English Pre-service Teacher in Indonesia - Kusuma Wardani, Tiara Aqwa Aningrum; Santosa, Imam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The European Framework for Educators' Digital Competence (DigCompEdu) is a scientifically solid framework that defines what it means to be digitally competent as an educator. DigCompEdu organizes 22 competencies into six areas. The emphasis is not on technical abilities. The framework aims to show how teachers may utilize digital technologies to improve and reinvent education and training. The preservice teaching experience is intended to create a controlled learning environment in which the future teacher may put the ideas and practices gained. Based on the 6 level of students of pre service teacher that have analyzed, the researcher identified 102 students of English education in the data. In the overall calculation, there are 33 universities which are 14 private and 19 public university. Then, 86 females and 16 males, the majority of the respondents in this study were female English education students. The majority of respondents (approximately 48 percent) have level B2, indicating that They fluently, creatively, and critically apply a variety of digital technologies to boost your professional operations. They actively choose digital technology for certain scenarios and attempt to comprehend the advantages and disadvantages of various digital tactics. They are inquisitive and open to new ideas, aware that there are many things they have yet to try. They employ experimentation to extend, structure, and consolidate your arsenal of techniques as a pre-service teacher.